تحليل الخطاب النقدي لمجموعة أرض البرتقال الحزين على أساس المنهج النقدي لنورمان فيركلف - نويدي عبدالوحيد; طالب پور دانا (University of Eloued جامعة الوادي, 2025)
وقعت دولة فلسطين بسبب موقعها الاستراتيجي، في براثن المستعمرین المعتدين منذ سنوات طويلة. لذلک فإن دور أدباء المقاومة لهذا البلد في الدفاع عن الحقوق الوطنية المفقودة لأبنائه كبير جدا، ومن الشخصيات المشهورة في الأدب الفلسطيني غسان كنفاني الذي كرس حياته للدفاع عن الوطن الفلسطيني المظلوم ومثله وقیمه العليا ، ورسم أجواء حياتهم الخانقة والحزينة. ومن أهم أنجازته روایة "أرض البرتقال الحزين" التي صورت تهجير الشعب الفلسطيني المظلوم ومشاكله، بما في ذلک الفقر والفساد والفجوة الطبقية الناجمة عن زحف اليهود الصهاينة على هذا البلد. يهدف المقال هذا إلى اكتشاف وتحديد المستویات الخطابية والدلالية المخفية في هذا العمل مستخدما الأسلوب الوصفي التحليل معتمدا على مكونات تحليل الخطاب النقدي لنورمان فيركلف. ومن أهم النتائج التي توصل إلیها المقال هو أن الکاتب باستخدام اللغة الواقعية والطلاقة والسلسة، تمكَّن من تقديم إيديولوجياته وخطاباته بطريقة فعالة وعملية في تصوير آلام ومعاناة واضطهاد الأمة الفلسطينية، وأنه قادرًا على التواصل بشكل جيد بين النص وسياقه، کما أن كفناني نفسه هو أحد المشاركين في الرواية وله دور فاعل فیها بهدف التشكيك في الهياكل الاجتماعية كعلاقات قوة باستخدام وساطة المعرفة السياقية، كما نرى بوضوح أن سلطة الخطابات الرسمية فعالة جدًا في إعادة إنتاج الخطابات من قبل بعض شخصيات القصة وتأثيرات القوة في أداء الخطابات وأفعالها. Because of its strategic location, the State of Palestine fell into the clutches of the aggressive colonialists many years ago. Therefore, the role of the writers of the resistance to this country in defending the lost national rights of its children is very great. Among the famous personalities in Palestinian literature is Ghassan Kanafani, who devoted his life to defending the oppressed Palestinian homeland, its ideals and its highest values, and drawing the suffocating and sad atmosphere of their lives. One of his most important achievements is the novel "Land of the Sad Orange", which depicts the displacement of the oppressed Palestinian people and their problems, including poverty, corruption and the class gap resulting from the encroachment of the Zionist Jews on this country. This article aims to discover and identify the hidden discursive and semantic levels in this work using the descriptive analysis method based on the components of Norman Fairclough's critical discourse analysis. Among the most important findings of the article is that the writer, using realistic, fluent and smooth language, was able to present his ideologies and discourses in an effective and practical manner in portraying the pain, suffering and oppression of the Palestinian nation, and that he is able to communicate well between the text and its context. Kafanani himself is one of the participants in the novel and has an active role in it with the aim of questioning social structures as power relations using the mediation of contextual knowledge, as we clearly see that the authority of official discourses is very effective in reproducing discourses by some of the characters of the story and the influences of power in the performance of discourses and their actions.
Keywords: غسان کنفاني،أرض البرتقال الحزین، فلسطین، نورمان فيرکلف، تحلیل الخطاب النقدي; Ghassan Kanfani The Land of sad Oranges; Palestine; Norman Fairclough; Discourse Analysis